2020
DOI: 10.2147/prbm.s280825
|View full text |Cite
|
Sign up to set email alerts
|

<p>Based on Computational Communication Paradigm: Simulation of Public Opinion Communication Process of Panic Buying During the COVID-19 Pandemic</p>

Abstract: Background and Aim: The spread of the COVID-19 pandemic has led to a number of instances of large-scale panic buying. Taking the COVID-19 pandemic as an example, this paper explores the impact of panic in uncertain environments on panic buying behavior. Under certain circumstances, the spread of rumors about shortage of goods is likely to cause large-scale panic buying. This paper focuses on the study of such panic buying caused by online rumors. Methods: Firstly, based on the improved BA network, this paper c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Not so in the postmodern condition' (p. 444), where panic is now associated with feelings of loss, cancellation, extermination and even hysteria. Li et al (2020) classify panic buying as a kind of impulsive consumer behaviour that is grounded in deep emotions such as human fear. Behavioural therapy research suggests that impulsive buying is a part of compulsive buying (Mueller et al, 2007).…”
Section: Towards An Under S Tand Ing Of the Panic Bu Ying Phenomenonmentioning
confidence: 99%
See 2 more Smart Citations
“…Not so in the postmodern condition' (p. 444), where panic is now associated with feelings of loss, cancellation, extermination and even hysteria. Li et al (2020) classify panic buying as a kind of impulsive consumer behaviour that is grounded in deep emotions such as human fear. Behavioural therapy research suggests that impulsive buying is a part of compulsive buying (Mueller et al, 2007).…”
Section: Towards An Under S Tand Ing Of the Panic Bu Ying Phenomenonmentioning
confidence: 99%
“…Li et al. (2020) classify panic buying as a kind of impulsive consumer behaviour that is grounded in deep emotions such as human fear. Behavioural therapy research suggests that impulsive buying is a part of compulsive buying (Mueller et al., 2007).…”
Section: Towards An Understanding Of the Panic Buying Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, other studies reported that PB was more common among people who were more worried about the COVID-19 pandemic and that social media possibly played a role in disseminating the worry, fear, and anxiety by showing images of empty shelves, which in turn produced a sense of scarcity and short supply ( 19 – 21 ). Studies from different settings have also reported that rumors regarding the shortage of supplies increased PB ( 22 – 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of the research on the dissemination of public opinion is based on the analysis of infectious disease models. Commonly used models are: Susceptible-Infected model (SI model) [5], Susceptible-Infected-Susceptible model (SIS model) [6], Susceptible-Infected-Recovered model (SIR model) [7], and Susceptible-Exposed-Infected-Recovered model (SEIR model) [8]. In these models, the nodes in the network are usually regarded as ordinary individuals in reality and are further subdivided into several categories.…”
Section: Introductionmentioning
confidence: 99%